Labor Epidural Analgesia to Cesarean Section Anesthetic Conversion Failure: A National Survey - Neel Desai; Andrew Gardner; Brendan Carvalho (Anesthesiology Research and Practice)
Background. If conversion of labor epidural analgesia to cesarean delivery anesthesia fails, the anesthesiologist can be confronted with a challenging clinical dilemma. Optimal management of a failed epidural top up continues to be debated in the absence of best practice guidelines. Method. All members of the Obstetric Anaesthetists’ Association in the United Kingdom were emailed an online survey in May 2017. It obtained information on factors influencing the decision to utilize an existing labor epidural for cesarean section and, if epidural top up resulted in no objective sensory block, bilateral T10 sensory block, or unilateral T6 sensory block, factors influencing the management and selection of anesthetic technique. Differences in management options between respondents were compared using the chi-squared test. Results. We received 710 survey questionnaires with an overall response rate of 41%. Most respondents (89%) would consider topping up an existing labor epidural for a category-one cesarean section. In evaluating whether or not to top up an existing labor epidural, the factors influencing decision-making were how effective the epidural had been for labor pain (99%), category of cesarean section (73%), and dermatomal level of blockade (61%). In the setting of a failed epidural top up, the most influential factors determining further anesthetic management were the category of cesarean section (92%), dermatomal level of blockade (78%), and the assessment of maternal airway. Spinal anesthesia was commonly preferred if an epidural top up resulted in no objective sensory block (74%), bilateral T10 sensory block (57%), or unilateral T6 sensory block (45%). If the sensory block level was higher or unilateral, then a lower dose of intrathecal local anesthetic was selected and alternative options such as combined-spinal epidural and general anesthesia were increasingly favored. Discussion. Our survey revealed variations in the clinical management of a failed epidural top up for cesarean delivery, suggesting guidelines to aid decision-making are needed.